WORLD MODELS OF DIGITAL CURRENCY REGULATION AND MODERN INITIATIVES OF CENTRAL BANKS - Khutorna , Myroslava; Tkachenko , Yuliya (Socio-economic relations in the digital society, 2021)
With the advent of digital currency, the most radical transformation in the field of monetary relations has taken place due to the emergence of private emission centers, and only this justifies profound changes in the system of modern monetary relations. Therefore, the world’s governments face the task of creating a legal framework for digital financial assets that would allow innovative projects to operate legally and attract investment, while controlling and neutralizing all associated risks (money laundering, tax evasion, etc.). For central banks, the emergence of not just private cryptocurrencies, including bitcoin, but more stablecoin, has become a significant challenge and impetus for the development of their own digital currency. The purpose of the study is to systematize current trends in the regulation of money market digitization and substantiate scenarios of its impact on the evolutionary transformation of the monetary system. It is proved that the nature and strength of the impact of digital currencies of central banks on the economic and financial spheres will directly depend on the demand for business and the population of the new tool, the possibilities of its widespread use. Regarding the latter, it depends on the model of sales of digital currencies of central banks, namely: 1) retail, in which the digital currency is available to a wide range of individuals and legal entities; 2) wholesale — only professional financial market participants have access to digital currency. In turn, the demand for digital currencies of central banks depends on factors of economic, socio-psychological, cognitive and legal nature, namely: 1) the method of determining the value of digital currency; 2) the level of its liquidity; 3) the possibility of establishing «instantaneous» payments; 4) availability of digital currency circulation infrastructure; 5) internal characteristics of digital currency; 6) trust in the central bank; 7) the level of digital and financial literacy of citizens; 8) the depth of digitalization of society; 9) legislative standardization of digital currencies; 10) methodology for accounting for digital currency subject to its tokenization.